2014
DOI: 10.1007/s11266-014-9481-y
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Community and Empowerment Among Young People: Understanding Pathways from Civic Participation to Social Well-Being

Abstract: Civic participation in community life and within community organiza-tions is generally considered as associated with positive outcomes for youth development and well-being. However, supportive empirical evidence on such benefits is still limited, as well as on the processes that may explain such positive outcomes. In this paper, we examined the impact of young people's participation different community and youth organizations on Social well-being, and the medi-ating role of Sense of community (SoC) and Empower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 41 publications
(56 reference statements)
6
51
0
3
Order By: Relevance
“…Interviewees also reported that associations on campus whose formal purposes were social, failed to overcome this intercultural discomfort, and were largely homogeneous. This failure is consistent with findings that participation in leisure and recreational associations have, at best, marginal value in contributing to the civic development of youth (Cicognani et al, 2015).…”
Section: Social Practices For Intercultural Comfort and Interactionsupporting
confidence: 89%
“…Interviewees also reported that associations on campus whose formal purposes were social, failed to overcome this intercultural discomfort, and were largely homogeneous. This failure is consistent with findings that participation in leisure and recreational associations have, at best, marginal value in contributing to the civic development of youth (Cicognani et al, 2015).…”
Section: Social Practices For Intercultural Comfort and Interactionsupporting
confidence: 89%
“…This is consistent with recent findings, that volunteering predicts youth's social well-being (Cicognani et al, 2014), which, as conceptualized by Keyes (1998), among other important dimensions, include social contributions.…”
Section: Discussionsupporting
confidence: 92%
“…However, research trying to find supportive empirical evidence for these ideas (especially with youth) is just starting to emerge. Researchers recently found that organizational membership of volunteering is significant in promoting youth's social well-being directly as well as through the increased sense of community and empowerment (Cicognani, Mazzoni, Albanesi, & Zani, 2014). However, empirical evidence, showing relationships between volunteering activities and contribution to self, family and community is highly limited.…”
Section: Introductionmentioning
confidence: 99%
“…McCowan, 2009;Hoskins et al, 2012a)-and research has shown how these experiences might have a positive impact on the socio-political development of young people (e.g. Ferreira et al, 2012;Zeldin et al, 2013;Cicognani et al, 2015). Therefore, it is not surprising that, as in other areas of public policy, NGOs have gradually become significant actors in this field, with a relatively close relationship with schools, teachers and pupils, as our surveys and interviews suggest, and also exerting some influence in the development of educational policies, as the evolution in England also demonstrates.…”
Section: Resultsmentioning
confidence: 99%